Xanthones from garcinia propinqua roots - Pornphimol Meesakul (2018)
Phytochemical investigation of Garcinia propinqua roots led to the isolation and identification of a new xanthone, doitunggarcinone D (1), together with 15 known compounds (2 V16). Their structures were elucidated by intensive analysis of spectroscopic data. Compounds 3, 6, 7, 14, 15 and 16 exhibited strong antibacterial activity against Bacillus subtilis TISTR 088 with MIC values in the range of 1-4 μg/mL. Compounds 3, 7, 10 and 14 also showed good antibacterial activity against B. cereus TISTR 688 with MIC values ranging from 4-8 μg/mL.